Exploring the Sport's Potential of Primitive Tribes - Sukendro; Fredrik Alfrets Makadada (Britain International for Academic Research (BIAR) Publisher, 2019)
The study aims to exploring the sport’s potential of primitive tribes. The habitation of primitive tribe is far into the forest which is difficult to reach by vehicles and must walk approximately 25 km from the nearest village or hamlet, this illustrates the endurance of their lungs very well. The result shows that coordination and agility are very good, because they have strength and agility in terms of climbing which in itself will have good arm strength and leg grip. Besides that they are proficient in hunting because hunting is the most important livelihood, they have the knowledge to succeed: the forest situation, natural signs, animal signs and how to catch them, because since childhood this generation has been trained to live deftly in the forest, of course has incredible speed and reaction and strength in getting hunted animals.